The mission of God's people : a biblical theology of the church's mission - Wright, Christopher J. H., 1947-; Wright, Christopher J. H. (Grand Rapids, Mich. : Zondervan, 2010)
Chris Wright's pioneering 2006 book, The Mission of God, revealed that the typical Christian understanding of "missions" encompasses only a small part of God's overarching mission for the world. God is relentlessly reclaiming the entire world for himself. In The Mission of God's People, Wright shows how God's big-picture plan directs the purpose of God's people, the church. Wright emphasizes what the Old Testament teaches Christians about being the people of God. He addresses questions of both ecclesiology and missiology with topics like "called to care for creation," "called to bless the nations," "sending and being sent," and "rejecting false gods." As part of the Biblical Theology for Life Series, this book provides pastors, teachers and lay learners with first-rate biblical study while at the same time addressing the practical concerns of contemporary ministry. The Mission of God's People promises to enliven and refocus the study, teaching, and ministry of those truly committed to joining God's work in the world. - Publisher.
Who are we and what are we here for? -- People who know the story they are part of -- People who care for creation -- People who are a blessing to the nations -- People who walk in God's way -- People who are redeemed for redemptive living -- People who represent God to the world -- People who attract others to God -- People who know the one living God and Saviour -- People who bear witness to the living God -- People who proclaim the Gospel of Christ -- People who send and are sent -- People who live and work in the public square -- People who praise and pray -- The journey so far and the journey ahead.
Includes bibliographical references and indexes.
Keywords: Mission of the church; Missions; Church work